Analisis Pertimbangan Majelis Hakim dalam Memutuskan Perkara Pembatalan Perkawinan Poligami - Rida Nabila (Jurnal Riset Hukum Keluarga Islam, 2023)
Abstract. In Islam marriage is called a sacred agreement or a very strong bond between a man and a woman to create a family that is sakinah mawaddah warahmah with the aim of worshiping Allah SWT. Basically, in marriage adheres to the principle of monogamy. But if a husband wants to have more than one wife, he must have permission from the first wife and permission from the Religious Court (Article 3 of Law No. 1 of 1974). The phenomenon that occurs as in the decision of the Ciamis Religious Court Number 2188/Pdt.G/2022/PA.Cms is the cancellation of polygamous marriages, even though the marriage is legally registered at the Office of Religious Affairs. The research used is qualitative with a normative juridical approach. The data analysis technique is library research which originates from the decision of the Ciamis Religious Court Number 2188/Pdt.G/2022/PA.Cms and interviews with one of the judges who decided the case. The request for annulment of a polygamous marriage was granted by the Panel of Judges basically because the husband did not follow the procedure for polygamy or having more than one wife as specified. Abstrak. Dalam Islam perkawinan disebut dengan perjanjian suci atau ikatan yang sangat kuat antara seorang laki-laki dan perempuan untuk mewujudkan keluarga yang sakinah mawaddah warahmah dengan tujuan sebagai ibadah kepada Allah swt. Pada asasnya dalam perkawinan menganut asas monogami.Tetapi apabila seorang suami ingin beristri lebih dari seorang maka harus ada izin dari istri pertama serta adanya izin dari Pengadilan Agama (Pasal 3 UU No. 1 Tahun 1974). Fenomena yang terjadi sebagaimana dalam putusan Pengadilan Agama Ciamis Nomor 2188/Pdt.G/2022/PA.Cms terjadi pembatalan perkawinan poligami, padahal perkawinan tersebut tercatat secara sah di Kantor Urusan Agama. Penelitian yang digunakan ialah kualitatif dengan pendekatan yuridis normatif. Teknik analisis data yaitu studi Pustaka yang bersumber dari putusan Pengadilan Agama Ciamis Nomor 2188/Pdt.G/2022/PA.Cms serta wawancara terhadap salah satu Hakim yang memutuskan perkara tersebut. Permohonan pembatalan perkawinan poligami dikabulkan oleh Majelis Hakim pada dasarnya karena suami tidak menempuh prosedur dalam berpoligami atau beristri lebih dari satu sebagaimana yang telah ditentukan.